Prognostic Value of Abnormal Liver Function Tests After Mechanical Thrombectomy for Acute Ischemic Stroke - Huang, Kangmo; Zha, Mingming; Xiao, Lulu; Gao, Jie; Du, Juan; Wu, Min; Yang, Qingwen; Liu, Rui; Liu, Xinfeng (Frontiers in Neurology, 2021)
Objective To determine the clinical significance of postoperative abnormal liver function test (ALFT) on the functional outcomes at 90 days in acute ischemic stroke (AIS) treated with mechanical thrombectomy (MT). Methods In this retrospective observational study, patients with AIS undergoing MT were enrolled from the Nanjing Stroke Registry Program and the multicenter Captor trial. A favorable outcome was defined as a modified Rankin Scale score 0-2 at 90 days. Predictive models were established by multivariable logistic regression. Improved predictive value of models was assessed by continuous net reclassification improvement (NRI) and integrated discrimination improvement (IDI). Additionally, multivariable logistic regression and restricted cubic spline were used to analyze dose-response correlations between the severity of ALFT and prognosis. Results Among 420 patients enrolled, 234 (55.7%) patients were diagnosed as postoperative ALFT after MT. Patients with postoperative ALFT had higher NIHSS score on admission (median, 18 vs. 15, P<0.001) and more pneumonia (65.4% vs. 38.2%, P<0.001) than those without postoperative ALFT. Postoperative ALFT, rather than preoperative ALFT, was independently associated with favorable outcome (adjusted odds ratio, 0.48; 95% confidence interval, 0.28-0.81; P=0.006). The improvement of predictive model after adding postoperative ALFT was significant (continuous NRI [value, 0.401; P<0.001], IDI [value, 0.013; P<0.001]). However, the restricted cubic spline indicated no evidence of a dose-response relationship between the severity of postoperative ALFT and prognosis. Conclusions In AIS patients treated by MT, postoperative ALFT was associated with more severe stroke and served as an independent predictor of worse prognosis at 90 days.